THE PLACE AND SIGNIFICANCE OF THE EPIC “OGUZNOMA” IN THE LITERATURE OF THE TURKISH PEOPLE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
In this article are given, the importance of the “Oguznoma” epic, which is one of the ancient written sources among the Turkic peoples, brief information about the epic, the personality and art of Oguz Khan, and the works created about him.